Croatian citizens and the European Union : value-based and attitudinal determinants - Landripet, Ivan (2008)
Introduction. "Attitude of Croatian citizens towards Croatia's membership in the European Union" was designed as a national study of attitudes, beliefs and awareness of Croatian citizens regarding the European Union, Croatia's accession to the EU and its membership in this supranational political and economic community. Combining two distinct approaches to studies of euro-dispositions and euro-sentiments – the rational/utilitarian and the symbolic, value/identity-based strategies, it encompasses different interconnected topics both directly or indirectly related to popular perception of euro-integrations (assessment of costs and benefits of the EU membership, comparison between economic, social and political situation in Croatia and the EU member states or perception of EU's ability to facilitate values it proclaims versus broader attitudinal and value-based structures such as political concepts, national pride and partisan preferences). The aim of the presentation is to provide an account of fundamental determinants of attitudes towards Croatia’s membership in the EU among Croatian citizens, one of the focal points of the study. Survey. The questionnaire that was implemented consisted of 45 instruments and the total of 260 items. The field part of the survey was conducted by the method of face-to-face interviews in May of 2007 on a nationally representative sample of adult citizens (N=1005 ; general population). This sample was construed as a multistage probabilistic sample with the random selection of respondents within households according to the Troldahl-Carter method. It enables generalizations on the target population with the maximal margin of error of ±3.1% (95% confidence level). Results. The central indicator, which also serves as a criterion in the multiple regression model, is support to Croatia’s EU membership. At the time, it amounted to 43%, with approximately one third of Croatian citizens being indecisive. Women were slightly more reserved and more prone to taking a neutral position, whereas there were significantly more men among both the firm opponents and supporters of EU membership. Citizens under 26 years of age proved least supportive of EU membership in contrast to those above 66, and vice versa. In terms of political preferences, apolitical and unaffiliated citizens comprise majority among the indecisive. These groups of respondents and the voters of the right-wing parties express the highest resistance to the EU membership. Support increases proportionately with the level of education, while religious attitudes do not seem to affect attitudes towards the EU membership. On the basis of factor analysis, insights into distributions of frequencies and internal consistency of the scale, we concluded that the question "What is your position on Croatia's accession to the EU membership?“ adequately represents all the basic indicators designed to measure personal stand on Croatia’s role in euro-integrations. Therefore we examined the relation between that particular indicator as a criterion and all the other segments of the study as predictors in a multiple regression analysis. The results show that 11 out of 28 latent dimensions are predictive of the criterion ; the model accounts for 48% of the variance. Generally speaking, respondents who believe that the EU is successful in solving different groups of problems within the member states are to a greater extent willing to support accession to the EU. Citizens who are more prone to stress any of the possible “cost aspects” of the membership (such as loss of sovereignty and cultural identity or greater threats of international terrorism) to a greater extent oppose accession, whereas those that emphasize one of the “benefit aspects”, political and economic prosperity, tend to be more supportive. It is also clear that respondents favoring pride in the Church, the Homeland War and Croatian history are less willing to support Croatia's accession to the EU. Among political concepts, multiculturalism and Europeism proved to be predictive of the criterion, the latter having greater positive impact on EU support than the first. It is important to note that none of the predictors related to the extent to which Croatia already meets the criteria for accession set by the EU entered the regression as relevant. It seems that the majority of citizens believe that everything is "already decided" and that it is solely up to Croatia to decide whether it will enter the EU or not. Absence of the EU-awareness sphere is also indicative. It means that both well- and ill-informed respondents assessed the criterion similarly, and since the percentage of those uninformed is much larger, it is doubtful whether the citizens have an objective picture about the integration processes and whether they qualify as political subjects capable of making a rational decision about Croatia’s accession to the EU.